Parental Depression and Associations with Parenting and Children’s Physical and Mental Health in a Sub-Saharan African Setting - Huang, Keng-Yen; Abura, Gloria; Theise, Rachelle; Nakigudde, Janet (Child Psychiatry & Human Development, 2017)
Depression is one of the most prevalent mental health challenges in low- and middle-income countries. However, the mechanisms of parental depression on children’s development are understudied in these countries. This study examined the prevalence of parental depression, contextual predictors of parental depression, and the associations between parental depression, parenting and children’s development in one of the Sub-Saharan African countries-Uganda. Three hundred and three Ugandan parents of young children were recruited and interviewed. Results indicated that about 28 % of parents were depressed. Contextual factors such as low educational attainment, food insecurity, low social support, and high number of children were associated with parental depression. Structural equation modeling also indicated that Ugandan parents’ depression was associated with less optimal parenting, and higher problem behavior, lower social competence, and poorer physical health and school functioning in children. Results provide several cross cultural consistency evidence in associations among parental depression, parenting, and child development.
Keywords: Parental depression; Parenting; Child mental health; Uganda; Sub-Saharan Africa; Low- and middleincome country